Sensitivity of Southern Ocean overturning to wind stress changes: Role of surface restoring time scales - Zhai, X; Munday, D (Elsevier, 2014)
The influence of different surface restoring time scales on the response of the Southern Ocean overturning circulation to wind stress changes is investigated using an idealised channel model. Regardless of the restoring time scales chosen, the eddy-induced meridional overturning circulation (MOC) is found to compensate for changes of the direct wind-driven Eulerian-mean MOC, rendering the residual MOC less sensitive to wind stress changes. However, the extent of this compensation depends strongly on the restoring time scale: residual MOC sensitivity increases with decreasing restoring time scale. Strong surface restoring is shown to limit the ability of the eddy-induced MOC to change in response to wind stress changes and as such suppresses the eddy compensation effect. These model results are consistent with qualitative arguments derived from residual-mean theory and may have important implications for interpreting past and future observations.